CLIMATE EMERGENCY: THE CHALLENGES OF FEELING, BEING, THINKING AND LIVING TOGETHER ON THIS TRAVEL ON PLANET EARTH/ EMERGÊNCIA CLIMÁTICA: OS DESAFIOS DE SENTIR, ESTAR, PENSAR E VIVER JUNTOS NESTE PERCURSO NO PLANETA TERRA - EDITORIAL - Carniatto, Irene; Silva, Harrysson Luiz da (International Journal of Environmental Resilience Research and Science, 2021)
Reflecting on Our Time “Stop to think about, stop to look around, stop to listen to the other, think carefully, look carefully, and listen carefully; stop to feel the other, feel carefully; dwelling on details, stop hearing your opinion, stop judging, stop your willing, stop with automatic actions, because you need to improve attention and tenderness, open your eyes and ears, talk about what happens to us, learn with no hurry, listen to the others, cultivate the art of getting together, be very quiet, be patient and give yourself some time and space (Jorge LARROSA, 2002, p.24. Our tradution).